Sp1 transcription factor represses transcription of phosphatase and tensin homolog to aggravate lung injury in mice with type 2 diabetes mellitus-pulmonary tuberculosis. Issue 4 (1st April 2022) - Zhao, Hongmei; Shi, Lian; Wang, Xiaohong; Yu, Xiuli; Wang, Danfeng
ABSTRACT: Type 2 diabetes mellitus (T2DM) can enhance the risk of mycobacterium tuberculosis (Mtb) infection and aggravate pulmonary tuberculosis (PTB). This study intended to explore the function of phosphatase and tensin homolog (PTEN) in T2DM-PTB and the molecules involved. Mice were treated with streptozotocin to induce T2DM and then infected with Mtb. The mice with T2DM had increased weight, blood glucose level, glucose intolerance and insulin resistance, and increased susceptibility to PTB after Mtb infection. PTEN was significantly downregulated in mice with T2DM-PTB and it had specific predictive value in patients. Overexpression of PTEN improved mouse survival and reduced bacterial load, inflammatory infiltration, cell apoptosis, and fibrosis in lung tissues. Sp1 transcription factor (SP1) was predicted and identified as an upstream regulator of PTEN. SP1 suppressed PTEN transcription. Silencing of SP1 enhanced mouse survival and alleviated the lung injury, and it promoted the M1 polarization of macrophages in murine lung tissues. However, further downregulation of PTEN increased protein kinase B (Akt) phosphorylation and blocked the alleviating roles of SP1 silencing in T2DM-PTB. This study demonstrates that SP1 represses PTEN transcription to promote lung injury in mice with T2DM-PTB through Akt activation. ABSTRACT: uf0001